Pendugaan Parameter Genetik Beberapa Genotipe Cabai Toleran pada Lahan Gambut - Deviona Deviona; Yunandra Yunandra; Dian Diana Ananta Budiati (Jurnal Agroteknologi, 2022)
The way to get superior varieties is by selection, namely through genetic parameters including diversity, heritability and genetic progress. This study aims to obtain information on the inheritance pattern of quantitative characters in several genotypes planted on peatlands. This study used a randomized block design consisting of 20 treatments and 3 replications so that 60 experimental units were obtained. Each experimental unit consisted of 20 plants and 10 plants were taken as samples. The results showed that the characters of red chili plant height, dichotomous height, crown width, fruit length, fruit diameter and weight per fruit can be used as selection criteria because they have wide diversity values, high heritability and high genetic progress which can be used as indicators of success. selection. Then, in cayenne pepper, all characters have a narrow genetic diversity value. Characteristics of flowering age, plant height, dichotomous height, crown width, fruit length, fruit diameter, weight per fruit and fruit weight per plant can be used as selection criteria because they have heritability values. and high genetic progress which can be used as indicators of successful selection.